Eksistensi Manajemen Pendidikan di Madrasah sebagai Pembentukan Karakter - Muhanna, Hafiz Attha; Mulyadi, Budi; Khairunnisa, Khairunnisa; Wicun, Dina (TSAQOFAH, 2022)
The purpose of this paper is to clarify the main problems that exist in Madrasa as follows. Obstacles to quality improvement. The result is Madrasa As an educational institution facing a dilemma. As an educational institution Madrasa, especially The era of local autonomy. In today's era of autonomy, it is one of the concepts that can: School-based management is used to improve the quality of education (SBM). This paper was published while Madrasa was sponsored. Ministry of Religion, the concept of school-based management (SBM) Adopted based on suitability as a strategy that Madrasa deals with Madrasa problem. Applying madrassa-based management It is intended to improve the quality of madrassa as an Islamic system.